CONSIDERAÇÕES ACERCA DO SISTEMA DE COTAS NA UNIVERSIDADE FEDERAL DE MATO GROSSO DO SUL E O PROCESSO DE IDENTIDADE DOS ALUNOS COTISTAS - JESSICA OLIVEIRA FERREIRA (2021)
This dissertation aims to trace the profile of black quota students at the Federal University of Mato Grosso do Sul (UFMS), with the central objective of analyzing the relationship between the process of self-declaration of these students and identity self-affirmation. In this study it is understood that the quota policy is configured as an important mechanism that provides opportunities for democratization of access to higher education. Thus, unveiling the profile of the quota student can contribute to the understanding that this affirmative action, in addition to opening space for access to higher education, also creates possibilities for self-recognition and self-affirmation of identity, especially for black quotaed youth, who often go through this process in the continuous construction of identity through various spaces. It was established as a cutout for this investigation the access through the racial lines of the quota policy, i.e., black students self-declared as black or mulatto at enrollment. To understand the access of the black population in higher education and its relation to the identity process, a theoretical reference and bibliographic survey was developed that promotes discussions in the field of studies of racial issues and public data, which allowed evidencing the struggle of the black population for the right to have access to higher education, and how the historical and geographic process explain and contextualize the implementation of the quota policy as a federal law in Brazil. To identify the profile of black quota-holding students, we conducted online interviews and used data provided by the Information and Communication Technology Agency (AGETIC/UFMS). To analyze and organize the results obtained, tables, graphs and charts were developed to identify the number of black quota students during the time period of the quota policy implementation and how this data relates to the identity of the students. The results of the research showed: the increase in the access of black students at UFMS, more than half self-declare as brown, male enrollment is greater than female, and most students before entering by racial quota had no dimension of the question about identity and self-declared without understanding or analyzing this issue, and the university and the spaces that it provides reflected densely on the process of self-declaration of identity